(untitled) (Research, Society and Development, 2021)
In cases of injuries in the oral cavity, the mouthwash comes in contact with the underlying gingival connective tissue and should have its cytotoxicity assessed. However, there is no available evidence if cells of elderly donors react differently during in vitro assessments of mouthwashes. This study aimed to compare the cytotoxicity evaluation of two different mouthwash types when assessed with primary gingival fibroblasts from either young and older donors. Primary cells were collected from two elderly patients (mean age 66.5 years old) and two young patients (mean age 27.5 years old). The primary cell culture was produced from gingival fragments and exposed for 24h in Perioxidin® and Oral B®. A control group was exposed to unconditioned culture media, representing 100% of cell survival (negative control), and 200mg/mL solution of latex fragments was used as a positive control due to its well-known toxicity. Both products presented similar dose-dependent cytotoxicity. In the toxic range, from 0.035% to 0.00035% for Perioxidin® and 0.06 to 0.0006% for Oral B®. The calculated IC50 values were very similar, with the exception of Oral B® tested with young cells, which presented a slightly higher toxic concentration (0.0523 mM). The statistical analysis shows no significant difference between tests with cells from young our elderly donors (p >0.05). These mouthwashes should should be used sparingly to prevent the spread of SARS-CoV-2. However, the use of age-matched cells during in vitro tests may not be necessary to predict differences in the biological response of the elderly to these products.